International R and D Spillovers and Institutions - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 2008)
The empirical analysis in "International R and D Spillovers" (Coe and Helpman, 1995) is first revisited by applying modern panel cointegration estimation techniques to an expanded data set that we have constructed for the purpose of this study. The new estimates confirm the key results reported in Coe and Helpman about the impact of domestic and foreign R and D capital stocks on TFP. In addition, we show that domestic and foreign R and D capital stocks have measurable impacts on TFP even after controlling for the impact of human capital. Furthermore, we extend the analysis to include institutional variables, such as legal origin and patent protection, in order to allow for parameter heterogeneity based on a country's institutional characteristics. The results suggest that institutional differences are important determinants of total factor productivity and that they impact the degree of R and D spillovers.